“Customer orientation assessment” within the automotive firms that are reaching the end-user - Gedik, Sidar (My University, 2007)
SON KULLANICIYA ERİŞEN OTOMOTİV FİRMALARINDA “MÜŞTERİ ODAKLILIK DEĞERLENDİRMESİ” Modern tedarik zinciri sayesinde firmalar ürün ve hizmet güncellemelerini hızla ve kötü sürprizlere olanak tanımadan gerçekleştirebilmektedirler. Bu zincir üzerinde domino etkisi yaratan ilk hareketi ise geri beslemeler sayesinde müşteri vermektedir. Müşteri etkisini gerektiğinde tasarım sürecine kadar geri götüren ve kendisini güncelleyebilen firmalar ise “müşteri odaklı” çalışma felsefesini hayata geçirebilmeyi başaranlardır.Bayiler gibi müşteri temas noktaları, müşterilerden en çok geri beslemenin alınabileceği yerler ve tüm firmaların özlem duyduğu “sadık müşteri” nin yaratılması için en uygun alanlardır. Firmaların üretim ve tasarım sürecine oranla çok daha az yatırımlar ile müşteri memnuniyetini artırabilecekleri birimler bu noktalardır. Bu amaçla müşteri ile temas biçimlerinin, içeriklerinin detaylı bir çalışma ile oluşturulması ve ardından da bu birimlerin performanslarının sürekli olarak takip edilmesi, geliştirilmesi gerekir. Yaklaşımımıza göre odağında müşterinin yer aldığı bir organizasyonun i.hizmete kolayca erişilebilen, ii.ihtiyaçların hızla tespit edildiği, iii.müşterinin orada yaşayacağı deneyim ile ilgili ön bilgi sahibi olabildiği, iv.verilen ön bilgilerin gerçekle örtüştüğü, v.öngörülemeyen durumlar ile ilgili ara bilgilendirme yapılan, vi.fayda&fiyat oranı tatmin edici kaliteli bir hizmet sunulan, vii.ileride tekrar tercih edileceği gibi başkalarına da önerilen, viii.verilen hizmetin kalitesinin sürekli geliştirilebilmesi için periyodik müşteri memnuniyeti ölçümü yapılan, ix.bu ölçümün sonuçlarının müşteri de dahil olmak üzere ilgili taraflarla düzenli olarak paylaşıldığı ortamlar sunabilmesi gerektiği noktasından hareket edilmiştir. Bu çalışma kapsamında yukarıdaki maddeleri içeren bir model önerilmiş ve son kullanıcıya erişen otomotiv firmaları bu model kullanılarak değerlendirilmiştir. Sorgulama sırasında 10 lu ölçek kullanılmıştır. 10 en pozitif, 1 en negatif yanıtı temsil etmiştir. 9 ve 10 – En pozitif yanıt aralığı, skor karşılığı 100 7 ve 8 – pozitif yanıt aralığı, skor karşılığı 50 6 ve daha düşük – nötr veya negatif yanıt aralığı, skor karşılığı 0

“CUSTOMER ORIENTATION ASSESSMENT” WITHIN THE AUTOMOTIVE FIRMS THAT ARE REACHING THE END-USER By the help of modernized supply chain, companies can realize product and service modifications rapidly and avoid unexpected surprises. The initial movement that affects the chain, like the domino effect, is feedback of the customer. The companies which are able to use the customer effect even in “design” process and improve their systems when needed are the ones that can realize “customer oriented” working philosophy. Customer contact points like dealers are the best resources of customer feedback and the most appropriate areas to create the expected “loyal customer”. In comparison to production and design processes, in these units, customer satisfaction can be increased with less investment. For this purpose, the way and content of the contact with a customer should be developed after a detailed study and subsequently their performance should be continuously followed and developed. According to our approach, an organization focusing customer should be offering environments where; i.service is easily accessible, ii.requirements are rapidly determined, iii.customer is informed in advance about the experience, iv.information matches realization v.customer is informed about unexpected situations, vi.a qualified service is offered with satisfying cost benefit ratio, vii.service is preferable and recommendable, viii.service is periodically measured in terms of customer satisfaction for continuous improvement, ix.the results of measurement are regularly shared with related sides including the customer. Within this study, an assessment model covering the issues above is offered and by using this model the workflow of automotive industry members that are reaching the end-user is evaluated. 10 point scale is used in questioning. 10 represents most positive, 1 most negative answer. 9 and 10 – Most positive answer interval, equivalent to 100 in score 7 and 8 – positive answer interval, equiv. 50 6 and less – neutral or negative answer interval, score equiv. 0 According to the result of the empirical study, the satisfaction index is calculated as 67.4 Satisfaction index values for each factor: General Quality and Attitudes of Service Staff66.3 Communication49.9 Accordance with Commitments80.0 First Right Repair91.6 All of the service attributes covered by “Communication” factor are the ones with satisfaction scores below the average. The satisfaction scores measured for “Advices for future”, “Informing about delay” and “After service communication” are lowest ones among the others. It is obvious that the first improvement area should be “Communication”.
Keywords: Müşteri Memnuniyeti; Müşteri Odaklılık; Otomotiv Endüstrisi; Otomotiv Firmaları